2014
DOI: 10.4049/jimmunol.1302953
|View full text |Cite
|
Sign up to set email alerts
|

TCR Scanning of Peptide/MHC through Complementary Matching of Receptor and Ligand Molecular Flexibility

Abstract: Although conformational changes in TCRs and pMHC molecules often occur upon binding, their relationship to intrinsic flexibility and role in ligand selectivity are poorly understood. Here we used NMR to study TCR-pMHC binding, examining recognition of the QL9/H-2Ld complex by the 2C TCR. Although the majority of the CDR loops of the 2C TCR rigidify upon binding, the CDR3β loop remains mobile within the TCR-pMHC interface. Remarkably, the region of the QL9 peptide that interfaces with CDR3β is also mobile in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 51 publications
6
55
0
Order By: Relevance
“…Our findings suggest a mechanism for TCR-ligand interaction, which may also be generalizable for ligand recognition by CD1c and CD1d molecules. It may also contribute to the fine-tuning of classical peptide-MHC recognition by TCR (42).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest a mechanism for TCR-ligand interaction, which may also be generalizable for ligand recognition by CD1c and CD1d molecules. It may also contribute to the fine-tuning of classical peptide-MHC recognition by TCR (42).…”
Section: Discussionmentioning
confidence: 99%
“…Contacts between TCR and MHC were identified using ContPro (54), the PyMOL script DistancesRH, and Accelrys Discovery Studio 4.1, using a 4.5-Å distance cutoff. We used this more liberal cutoff distance (compared with the more common 4 Å) to better account for coordinate error and the nonstatic nature of the protein interfaces (55,56). TCR-pMHC complexes were superimposed by the PyMOL pair fit function, fitting the α carbon of residues 1-180 of the MHC protein.…”
Section: Methodsmentioning
confidence: 99%
“…Toward this end, we prepared samples of the mini-H2-L d construct refolded in vitro with two different peptides. In particular, we used the QL9 peptide (21) (also employed previously to study binding to the 2C TCR (13,16,17)) and a high affinity NIH self-peptide. Although initially, both samples gave well dispersed two-dimensional TROSY spectra, each indicative of a properly conformed peptide⅐ MHC-I complex, the sample prepared with QL9 deteriorated within 1 week at 25°C.…”
Section: Direct Interaction Between M06 and H2-l D Mhc-i-initialmentioning
confidence: 99%
“…Subsequent structural characterization showed that this molecule preserves the binding epitopes for T cell recognition in their native orientation, as indicated by co-crystal structures of several peptide⅐MHC-I/TCR complexes (15). More recently, solution NMR studies of the 2C/mini-H2-L d system explored recognition dynamics at the MHC-I/TCR interface (16,17).…”
mentioning
confidence: 99%